Struktur Modal, Profitabilitas, dan Nilai Perusahaan: Studi Moderasi Oleh Keputusan Investasi dan Kebijakan Dividen - Ezar Widyadhana; Taufik Akbar (Owner : Riset dan Jurnal Akuntansi, 2026)
In a competitive business landscape, increasing corporate value becomes crucial. Previous studies has not extensively analyzed the simultaneous moderating roles of investment decisions and its payout procedures, particularly in non- financial businesses within the BISNIS 27 index. Therefore, The present research seeks at analyzing the impact of both capital layout and profitability of the firm’s value influenced by investment decisions and dividend policy. Using the quantitative strategy, secondary Information gathered from accounting records among non-bank business entities in BISNIS 27 index for the period 2022-2024 were analyzed using panel data regression and Moderated Regression Analysis (MRA). The results showed that the equity structure (DER) had a significant positive effect on firm value (PBV), while profitability (ROA) did not have a direct significant influence. Investment decisions (PER) are proven to Highly moderate the influence Structure of capital and the profitability with company priorities, strengthening the relationship. Conversely, Governance of dividends (DPR) does not moderating on profitability, but it can moderate capital structure. Simultaneously, the regression model is significant, explaining 25.8% of the variation in firm value. This insight points out how crucial to debt management and strategic investment in shaping corporate value.